Exploration of the Use of Digital Learning Media in Enhancing Children's Learning Motivation at TK Negeri 11 Samatiga : A Library Research - RINIYULISTYA YULISTYA (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study explores the utilization of digital learning media in enhancing children's learning motivation at TKN 11 Samatiga. With the rapid advancement of technology and its integration into educational settings, this research aims to investigate how digital tools can foster a more engaging and motivating learning environment for young learners. The study employs a library research approach, analyzing existing literature on digital media in early childhood education and its impact on children’s motivation to learn. Through a comprehensive review of various studies, this research identifies key digital resources, pedagogical strategies, and the role of educators in effectively implementing technology in the classroom. The findings suggest that the incorporation of digital learning media not only stimulates children's interest but also promotes deeper engagement, creativity, and independent learning. Additionally, the research highlights potential challenges and considerations for educators in using digital tools effectively. Ultimately, this exploration contributes valuable insights into the significance of digital learning media as a catalyst for motivating young learners in a kindergarten setting.